2020
DOI: 10.3389/fmicb.2020.00349
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Posaconazole Prophylaxis for Fungal Disease in Hematology Patients Treated With Chemotherapy and Transplantation: An Open-Label, Prospective, Observational Study

Abstract: Background: Posaconazole (PCZ) is used prophylactically to prevent invasive fungal infections (IFIs) in patients with hematological malignancies. Objective: To evaluate the cutoff serum concentration of PCZ for successful IFI prophylaxis in Chinese subjects. Patients and Methods: A total of 74 patients treated with induction chemotherapy (n = 10) and allogeneic hematopoietic stem cell transplantation (HSCT) (n = 64), who received PCZ prophylactically as an oral suspension for >7 days, were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Logistic regression analysis revealed that the PCZ C min value of 0.76 µg/mL was associated with >80% probability of successful therapy ( Wang et al, 2014 ). Similar to a prospective study of PCZ prophylaxis of IFIs in patients with hematological diseases [the success rate was (64/74) 86.5%] ( Li et al, 2020 ), and a randomized clinical trial for prophylaxis against IFIs [the success rate was (85/91) 93.5%] ( Jang et al, 2010 ), the current study found that 83.3% of patients (30/36) successfully responded to PCZ prophylaxis. In agreement with the previous study ( Chau et al, 2014 ), a PCZ C min of 1.0 µg/mL was chosen as the lower limit to treatment of a proven, probable, or possible IFI, and the logistic regression model showed that this C min was associated with a probability of successful response of 80.5% ( Figure 3B ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Logistic regression analysis revealed that the PCZ C min value of 0.76 µg/mL was associated with >80% probability of successful therapy ( Wang et al, 2014 ). Similar to a prospective study of PCZ prophylaxis of IFIs in patients with hematological diseases [the success rate was (64/74) 86.5%] ( Li et al, 2020 ), and a randomized clinical trial for prophylaxis against IFIs [the success rate was (85/91) 93.5%] ( Jang et al, 2010 ), the current study found that 83.3% of patients (30/36) successfully responded to PCZ prophylaxis. In agreement with the previous study ( Chau et al, 2014 ), a PCZ C min of 1.0 µg/mL was chosen as the lower limit to treatment of a proven, probable, or possible IFI, and the logistic regression model showed that this C min was associated with a probability of successful response of 80.5% ( Figure 3B ).…”
Section: Discussionsupporting
confidence: 74%
“…However, real-world data in this field is limited, especially in Asian populations. One Chinese study suggested that the concentration of PCZ affects the probability of response to prophylaxis of fungal infections, but factors, other than PPIs, affecting PCZ concentrations were not investigated so far ( Li et al, 2020 ). One South Korea study suggested that hypoalbuminemia influences PCZ concentrations, but the concentration-to- response relationship was not explored ( Oh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all patients in the FAS were treated in an inpatient setting at the time of MAT index/enrollment; only two patients in the voriconazole group were treated in an outpatient setting. The median length of the initial hospital stay was 26 days (95% CI [25][26][27], ranging from 23 days (95% CI [21][22][23][24][25][26] in the isavuconazole group to 28 days (95% CI [26][27][28][29][30] in the posaconazole group (Table 6). Overall, around 27% of patients who were hospitalized at index/ enrollment were in the ICU, ranging from 13.6% of patients in the posaconazole group to 36.6% of patients in the isavuconazole group.…”
Section: Secondary Endpoint: Healthcare Resource Utilizationmentioning
confidence: 99%
“…Finally, routine quanti cation of therapeutic drug monitoring for posaconazole is not carried out in clinical practice in this study. In the literature, the plasma concentration of posaconazole was related to the incidence of IFD [23]. This potential posaconazole serum concentration differences would make data analysis more di cult and complex.…”
Section: Discussionmentioning
confidence: 99%